Implementasi Fiqh Jinayah dalam Qanun Nanggroe Aceh Darussalam: Suatu Tinjauan Historis, Yuridis, Filosofis dan Sosiologis - Mubarok, Nafi' (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2021)
This article describes the implementation of fiqh jinayah in the national criminal law system. The discussion focused on: (1) the existence of fiqh jinayah in Indonesia's national criminal law and (2) the implementation of fiqh jinayah in Indonesia in the Qanun of Nanggroe Aceh Darussalam. At the end of the article, it is concluded that the study of the implementation of fiqh jinayah in the Qanun NAD can be accomplished by examining the existence and implementation of several aspects. In the aspect of historical existence, fiqh jinayah has been an entity of NAD people's life for a long time, and juridically, fiqh jinayah is one of the sources of material law for the formation and renewal of national criminal law, in addition to legal recognition and regulation of fiqh jinayah. While in the implementation aspect, the application of fiqh jinayah philosophically assumes values ​​that exist and adapt to the conditions of the Indonesian legal system. Sociologically some situations support the implementation of fiqh jinayah in the NAD Qanun; in addition, the application of fiqh jinayah has proven to be effective. as an effort to protect the community in minimizing the occurrence of crime.